2019
DOI: 10.1016/j.micinf.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Organelle dynamics and viral infections: at cross roads

Abstract: Viruses are obligate intracellular parasites of the host cells. A commonly accepted view is the requirement of internal membranous structures for various aspects of viral life cycle. Organelles enable favourable intracellular environment for several viruses. However, studies reporting organelle dynamics upon viral infections are scant. In this review, we aim to summarize and highlight modulations caused to various organelles upon viral infection or expression of its proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 186 publications
0
49
0
Order By: Relevance
“…Mitochondria are cell organelles that play a key role in the maintenance of cellular homeostasis. They are involved in numerous functions and signaling pathways such as energy metabolism, innate immunity, calcium homeostasis, apoptosis, aging, and others [10]. Mitochondria are not static, but dynamic organelles involved in adaptation to changes in the metabolic environment of cells as well as their survival or death, in order to maintain the quality of mitochondrial function.…”
Section: Mitochondrial Dynamics: Role In Cell Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria are cell organelles that play a key role in the maintenance of cellular homeostasis. They are involved in numerous functions and signaling pathways such as energy metabolism, innate immunity, calcium homeostasis, apoptosis, aging, and others [10]. Mitochondria are not static, but dynamic organelles involved in adaptation to changes in the metabolic environment of cells as well as their survival or death, in order to maintain the quality of mitochondrial function.…”
Section: Mitochondrial Dynamics: Role In Cell Physiologymentioning
confidence: 99%
“…Viruses modify the intracellular number and distribution of mitochondria either to get energy for replication or to prevent the release of apoptosis mediators [10]. It has been reported that hepatitis B virus (HBV) infection produces mitochondrial fission and subsequent mitophagy.…”
Section: Mitochondrial Dynamics and Viral Infectionmentioning
confidence: 99%
“…All enveloped viruses must modulate cellular membrane systems throughout their lifecycles, from hijacking endosomes for entry and diverting cellular membrane compartments for replication, to taking over cellular secretion systems for viral egress and immune evasion (Welsch et al, 2007;Mercer et al, 2010;Glingston et al, 2019). As exclusively cytoplasmic replicating viruses, poxviruses, are no exception to this rule (Moss, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These changes to the intracellular environment arise as a consequence of the manipulation of a range of cellular functions and are intimately linked to key processes in the viral replication cycle such as virus assembly and egress [1][2][3]. However, there is relatively little understanding of the dynamics of morphological changes of infected cells and how they relate to distinct phases of the herpesvirus replication cycle [4].…”
Section: Introductionmentioning
confidence: 99%